Pengaruh Pengetahuan Mitigasi Bencana Tanah Longsor Terhadap Kesiapsiagaan Siswa Di Kecamatan Balikpapan Utara - Aprilla, Nasywa Syifa; A, Doni; Rafli H, Muh.; Akmal I, Muh; A. N. R, Ocktavianus; Daffa H.Z, Muh; Yoga, I Kadek; Raghid H'Z, Muh; Indriani, A. M. (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2025)
Landslides pose a serious threat, causing significant property damage and loss of life. This study aimed to determine the extent to which knowledge of landslide mitigation can enhance students' preparedness. A survey of approximately 700 middle school students in North Balikpapan district was conducted. The results showed a positive correlation between knowledge of landslide mitigation and students' preparedness. The higher the students' knowledge, the better prepared they were to face landslides. This study concludes that increasing students' knowledge about landslide mitigation can effectively improve their preparedness.